Morphological Errors of Macedonian Speakers in Learning Slovenian: An Analysis of Nouns and Adjectives - Pavletić, Nika; Šumenjak, Klara (Slavistična prepletanja 6, 2025)
The article examines challenges in the acquisition of Slovenian as a foreign language by Macedonian speakers, focusing on specific morphological features of nouns and adjectives where differences between the two languages are evident. Although Slovenian and Macedonian are related languages, they differ significantly at the systemic linguistic level. These differences impact the process of learning Slovenian and frequently result in negative language transfer. This version maintains academic phrasing while clearly emphasizing the focus on nouns and adjectives. It works well in a linguistic context and highlights the article's scope effectively. Between 2019 and 2022, language testing was conducted with 53 students at the University of Primorska who had Slovenian proficiency at the basic level. The test focused on assessing knowledge of selected grammatical categories in nouns and adjectives. The results revealed that the majority of errors occurred in areas where Macedonian lacks equivalent structures, such as declensions, stem extensions, synthetic adjective gradation, and vowel alternation following soft consonants. Common errors included errors in stem extensions (e.g., prostorja, sirjom, pulovere), the use of vocative forms (e.g., profesorice), and incorrect adjective gradation (e.g., najvisoka). The study provides insights into the most frequent errors made by Macedonian speakers learning Slovenian as a foreign language.